Minor Tibetan Texts: 1. The song of the Eastern Snow-mountain - Manen, Johan van, 1877-1943 (Salt Lake City, UT : Project Gutenberg, 2022)
"Minor Tibetan Texts: 1. The Song of the Eastern Snow-mountain" by Johan van Manen is an academic work that appears to have been written in the early 20th century. This text forms part of a series that aims to delve into lesser-known Tibetan literature, particularly focusing on the cultural and religious significance of Tibetan songs and prayers. It is likely centered around the historical context and teachings related to Tsoṅkapa, a notable figure in Tibetan Buddhism, and his followers. The opening of the text sets up a foundational framework for understanding the poem's significance. It opens with a prefatory note that addresses the lack of knowledge surrounding Tibetan literature, outlining the challenges faced by scholars in translating and understanding the language and its idiomatic nuances. Following this, the introduction provides insights into the historical figures associated with Tibetan Buddhism, particularly the three main teachers in lamaism, and hints at the content of the poem itself, which pays homage to these influential figures and reflects on their teachings. The text also notes the complexities involved in the transcription of Tibetan materials and the author's dedication to preserving the accuracy of the language for future scholarship. (This is an automatically generated summary.)
Release date is 2022-02-20
Jeroen Hellingman and the Online Distributed Proofreading Team at https://www.pgdp.net/ for Project Gutenberg (This file was produced from images generously made available by The Internet Archive/Canadian Libraries)
Keywords: Prayer -- China -- Tibet Autonomous Region -- Buddhism; Buddhist literature, Tibetan; Tibetan language -- Texts